PERAN MEDIA DIGITAL DALAM MEMBENTUK POLA KOMUNIKASI MASYARAKAT MODERN DI ERA MEDIA SOSIAL - Asidiq, Muhamad Firas; M, Supriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital media, particularly social media, has brought significant changes to the communication patterns of modern society. This study aims to analyze the role of digital media in shaping communication patterns in the social media era and its resulting impacts. The method used is library research with content analysis techniques applied to various relevant literature sources. The results show that digital media has transformed communication patterns from face-to-face interaction to technology-based communication that is more flexible, fast, and not limited by space and time. Social media also encourages interactive and participatory communication, while fostering a more open and democratic communication character. However, the use of digital media also has negative impacts, such as decreased quality of interpersonal communication, reduced emotional engagement, and issues like the spread of inaccurate information and low communication ethics. Therefore, digital literacy and wise use of media are necessary to optimize the benefits of digital media in the social life of modern society.